Government grants: an analysis of the relationship between the level of disclosure and the characteristics of publicly traded brazilian companies (Revista Brasileira de Contabilidade e Gestão, 2018)
The objective of this study was to verify the relationship between the level of disclosure of government grants and the characteristics of Publicly Traded Brazilian Companies. For this purpose, a checklist was prepared, based on technical pronouncement CPC 07 (R1), addressing the requirements established by said pronouncement, regarding the correct disclosure of government grants in the financial statements and explanatory notes. Through the checklist it was possible to measure the level of disclosure of the companies analyzed and to relate to the main characteristics of the companies, such as: i) auditing company, ii) results of the fiscal year, and iii) subsector classification. In addition, a ranking was made with the highest and lowest levels of disclosure found in the sample. The documents analyzed were: The Statement of Income (DRE), Balance Sheet (BP) and the explanatory notes for the year 2016 of 260 companies that presented some type of government grant in their financial statements. The results of the research showed that the majority of Brazilian companies have a low level of disclosure of government grants, in which only 26 sample companies obtained a disclosure level equal to or greater than 50%. It was also concluded that the results of the research do not suggest a tendency of relation between the characteristics analyzed (audit firm, result of the exercise and subsector) with the low level of disclosure of the companies.
Keywords: government grant; government grants; CPC 07 (R1); disclosure